Contextualized language teaching creating oral communication lesson exemplars based on perceived body images of students - Mercado, Jaime II G.
Language instruction has come a long way, from being purely grammar-based to integrating more practical and real-world applications. One pedagogical approach that has gained traction in recent years is contextualization. This qualitative study explored the flexibility of contextualization as a pedagogical approach by integrating the perceived body images of the senior high school students into the contextualized lesson exemplars int he topic 'The Speech Writing process' in an Oral Communication course. This was conducted in one secondary school in Iloilo in the first semester of the school year 2023-2024. Using purposive sampling, six grade 11 senior high school students were identified as the study participants. Data were gathered using the students' essays, supplemented by a focus group discussion, and were analyzed using the NVivo software. The analysis revealed that the students have positive and negative perceived body images. These were reflected in their perceptions of physical attractiveness, perception of being beautiful and handsome, and perception of being unattractive. Further, from these perceptions, contextualization needs such as concerns about their physical attributes, the influence of family friends, and media, and the role of self-awareness in achieving positive body imae were identified. From these needs, five contextualized lesson exemplars in the topic 'The Speech Writing Process' were made to illustrate how contextualization was made possible by integrating the perceived body images of the students. This study offers theoretical implications that may explore the potential for fostering deeper engagement, critical thinking, inclusivity, self-reflection, and personal growth within the Contextualized learning and Teaching (CLT) framework. In addition, practical implications emphasized the potential for enhancing content richness, critical analysis, audience engagement, inclusivity, and self-expression in students' speech-writing endeavors.Finally, this study proposes several measures for fostering a more positive self-image among students which may include the incorporation of self-image positivity programs into educational curricula, the integration of body image education, cultural sensitivity training for teachers, partnering with mental health experts, initiatives aimed at research and development, introducing media literacy into learning, and encouraging community participation in advocacy efforts.